An inverse causal association between genetically predicted vitamin D and chronic obstructive pulmonary disease risk - Lu, Kening; Tan, Jiang-Shan; Li, Tian-Qi; Yuan, Jiaqin; Wang, Han; Wang, Wenting (Frontiers in Nutrition, 2023)
Aim: Observational studies have reported that levels of vitamin D were associated with the incidence of chronic obstructive pulmonary disease (COPD), but the relationship between them may have been confounded in previous studies. In this study, we aimed to determine the relationship between the levels of 25-hydroxyvitamin D (25OHD) and the risk of COPD by two-sample Mendelian randomization (MR) analysis. Methods: Summary statistics for 25OHD and COPD in this study were obtained from the EBI (n= 496,946) consortium and Finn (n= 187,754) consortium. MR was adopted to explore the effect of the genetically predicted levels of 25OHD on the risk of COPD. Based on three assumptions of MR analysis, inverse variance weighting was used as the main analysis. To make our results more robust and reliable, MR Egger's intercept test, Cochran's Q test, funnel plot, and "leave-one-out" sensitivity analysis was used to assess the potential pleiotropy and heterogeneity in this study. Then, colocalization analysis and MR Steiger approaches were used to estimate the possible directions of estimates between them. Results: Our results showed that each 1 standard deviation (SD) increase in the genetically predicted 25OHD level was associated with a 57.2% lower relative risk of COPD [odds ratio (OR): 0.428, 95% Cl: 0.279-0.657, P= 1.041×10-4], and the above association was also verified by maximum likelihood (OR: 0.427, 95% Cl: 0.277-0.657, P= 1.084×10-4), MR‒Egger (OR: 0.271, 95% CI: 0.176-0.416, P= 2.466×10-4), MR-PRESSO (OR: 0.428, 95% Cl: 0.281-0.652, P= 1.421×10-4) and MR-RAPS (OR: 0.457, 95% Cl: 0.293-0.712, P= 5.450×10-4),. Furthermore, colocalization analyses (rs3829251, PP.H4=0.99) and MR Steiger (“TRUE”) also showed a reverse association between them. Conclusion: Our findings provide evidence for a reverse association between genetically predicted 25OHD levels and COPD risk. Taking measures to supplement 25OHD may help reduce the incidence of COPD.